An organic-inorganic hybrid strategy to fabricate highly dispersed Fe2C in porous N-Doped carbon for oxygen reduction reaction and rechargeable zinc-air battery. (15th August 2022) - Guan, Xiya; Li, Haibo; Li, Ruiqing; Zeng, Suyuan; Li, Rui; Yao, Qingxia; Chen, Hongyan; Zheng, Yao; Qu, Konggang
Abstract: Transition metal-based carbon composites have shown great potentials as electrocatalysts due to their abundance and low cost. However, the sintering from the migration and aggregation of metal species during pyrolysis would compromise the catalytic activity or even lead to the deactivation of the catalyst. Herein, taking advantage of polydopamine (PDA) and silane (3-aminopropyltriethoxysilane, APTS), one novel organic-inorganic hybrid strategy was firstly employed to synthesize highly dispersed Fe species embedded in N-doped porous carbon nanosheet (Fe, N–PCN). Thereinto, organic PDA can provide universally robust adhesion, inner porous structure with enlarged surface area can be achieved from inorganic SiO2, the mutual confinement from PDA-derived carbon and SiO2 facilitates the formation of highly dispersed, exposed active sites. Consequently, the newly-prepared Fe, N–PCN displays excellent alkaline ORR activity matching with Pt/C together with better stability and selectivity. Theoretical computations unclose the C atoms close to N (CN ) on carbon as active sites with the optimized adsorption/desorption strength towards ORR intermediates, tailored by the interfacial electron transfer between Fe2 C and N-doped carbon. Meanwhile, the assembled rechargeable zinc–air battery exhibits large peak power density (119.7 mW cm −2 ), specific capacity (775 mAh gZn −1 ) and robust charge-discharge durability (250 h, 1500 cycles), overmatching Pt/C and previously studied Fe-based materials. Graphical abstract: A proof-of-concept organic-inorganic hybrid strategy was firstly proposed to synthesize highly dispersed Fe2 C embedded into N-doped porous carbon nanosheet with inner porous structures and enlarged surface area, displaying comparable ORR activity with Pt/C and superior rechargeable zinc–air battery performance. Image 1 Highlights: An organic-inorganic hybrid strategy was first explored for metal/carbon composite. Highly dispersed Fe species with inner porous structure and enlarged surface area. Excellent ORR activity matching with Pt/C and zinc–air battery performance. C active sites adjacent to N for ORR tailored by the interfacial electron transfer.